Seawater for the novelty era of communications-opportunities and challenges - Elmutasim, Imadeldin Elsayed; Izzeldin Ibrahim, Mohamed Abdelaziz; Bilal, Khalid Hamid (JATIT, 2022)
Seawater is an abundant resource that could play an indispensable role in many applications involving electrical conductivity, monitoring security, improved battery power efficiency, and as an antenna transmitter and receiver. Thus in certain circumstances seawater could serve a useful purpose for service providers when other materials are unavailable. The study assesses the comparative strengths and weaknesses of different underwater techniques for creating a large-scale practical utilization while the contribution is to offer a computation method when considering seawater connectivity. The objective of the comprehensive investigation is to examine the signal behaviour for underwater communication to give a remarkable way for developing the new upcoming technology era, particularly in terms of water communication technology. A significant result shows the parameters of the permittivity, salinity, and frequency could notably affect the underwater communication techniques in terms of signal magnitude, phase, and delay rate. The higher frequency leads to more fluctuation in magnitude, while degradation begins after 10 KHz and shows more slope gradient after 100 KHz in the signal phase, added to the notable delay rate that would start after 100 Hz severely.